2018
DOI: 10.4174/astr.2018.94.4.174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prophylactic and therapeutic effects of ruscogenin on acute radiation proctitis: an experimental rat model

Abstract: PurposeRadiation proctitis (RP) is inflammation and damage to the rectum, manifested secondary to ionizing radiation utilized for treatment. In this study, we evaluated the anti-inflammatory therapeutical and protective effects of ruscogenin in a model of acute RP.MethodsThirty-two Sprague-Dawley rats were divided into 4 groups (n = 8) as sham, control, treatment, and prophylaxis groups. Prophylaxis group and treatment group were dosed ruscogenin by oral gavage for 14 days pre- and postradiation. At the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…TNF-α is a cellular signaling protein involved in inflammation and one of the cytokines constituting the acute phase response to inflammation and is mainly produced by activated macrophages [14]. Studies have shown that the expression of TNF-α is significantly increased both in the serum of RP patients [15] and in rectal tissues of RP rat models [16]. IL-4 and IL-10, both anti-inflammatory cytokines, are secreted by Th2 cells, which down-regulate the inflammatory response by inhibiting the proliferation of Th1 cells, blocking the production of pro-inflammatory cytokines and reducing the function of antigen-presenting cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a cellular signaling protein involved in inflammation and one of the cytokines constituting the acute phase response to inflammation and is mainly produced by activated macrophages [14]. Studies have shown that the expression of TNF-α is significantly increased both in the serum of RP patients [15] and in rectal tissues of RP rat models [16]. IL-4 and IL-10, both anti-inflammatory cytokines, are secreted by Th2 cells, which down-regulate the inflammatory response by inhibiting the proliferation of Th1 cells, blocking the production of pro-inflammatory cytokines and reducing the function of antigen-presenting cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the positive effect of hydrolyzed DNA-RNA was not synergistic in combination with other tested bioactive molecules, such as hyaluronic acid, β-Glucan, allantoin, bisabolol, ruscogenin, and several essential oils ( Table 2 ). The aforementioned molecules were proven to have anti-inflammatory, antioxidant, and anti-aging activity, helping in wound healing, epithelial regeneration, and extracellular matrix regeneration [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. However, a formulation containing these bioactive molecules in addition to hydrolyzed DNA and RNA did not yield a higher protective effect than the formulation containing DNA and RNA alone.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] In the literature, animal experiments have used many drugs that are thought to prevent radiation damage, including ozonated olive oil, sildenafil, and ruscogenin. [ 4 - 6 ] Hyaluronic acid (HA) and chondroitin sulfate (CS), which are components of the urothelial mucosa layer. İntravesical HA and chondroitin sulfate combination (HA/CS) (iAluRil ® , Aspire Pharma) are applied in the treatment of urinary tract infections and bladder pain syndrome.…”
Section: Introductionmentioning
confidence: 99%